Relationship between adverse childhood experiences and musculoskeletal pain: the mediating effect of depressive symptoms - Yun Jin; Haiyan Lin (BMC Psychology)
Abstract Background Adverse Childhood Experiences (ACEs) are linked to long-term health impacts, including musculoskeletal pain (MSP). However, the role of depressive symptoms (DS) as a mediator in this relationship is not well understood. This study examines the role of DS as a mediator in this relationship among middle-aged and older Chinese adults. Methods Utilizing data from 11,905 participants in the China Health and Retirement Longitudinal Study (CHARLS). ACEs were assessed using 12 indicators, MSP was determined based on reported pain locations (spine, upper limbs, and lower limbs), and DS were measured using the 10-item Center for Epidemiological Research Depression Scale (CESD-10). Logistic regression was used to evaluate the associations between ACEs and MSP, DS. Mediation analysis was conducted to assess the mediating effect of DS between each ACE and MSP. Results ACEs were significantly associated with increased odds of MSP (OR: 1.233, 95% CI: 1.196–1.270), and DS (OR: 1.326, 95% CI: 1.287–1.367). Among individual ACEs, household mental illness showed the strongest association with MSP (OR: 1.824, 95% CI: 1.601–2.077). Mediation analysis showed that DS partially mediated the relationship between seven types of ACEs and MSP, including physical abuse, family violence, peer bullying, unsafe community environment, parental disability, death of siblings, and parental mental health, with the proportion mediated ranging from 34.6 to 64.8%. Conclusion Our study demonstrates that ACEs are significantly associated with MSP in the elderly population, and that DS partially mediates the relationship between ACEs and MSP.